2008
DOI: 10.1111/j.1945-5100.2008.tb01024.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlated isotopic and microstructural studies of turbostratic presolar graphites from the Murchison meteorite

Abstract: Abstract-We present data from TEM and NanoSIMS investigations of Murchison (CM2) KFC1 presolar graphites. TEM examinations of graphite ultramicrotome sections reveal varying degrees of graphite disorder, leading to distinctions between well-graphitized onions, more turbostratic platy graphites, and the most disordered cauliflower graphites. Aside from their larger size, platy graphites are roughly similar in isotopic composition and in internal grain properties to the well-graphitized onions. Most carbide-cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 37 publications
1
33
0
Order By: Relevance
“…Lattice fringes often cross entire grains, providing evidence that these crystals are not mixtures of disordered graphite, graphene, and graphane, as observed in other natural and anthropogenic nanoscale carbons (e.g., refs. [37][38][39][40][41][42]. A number of other internal textures were observed.…”
Section: Resultsmentioning
confidence: 96%
“…Lattice fringes often cross entire grains, providing evidence that these crystals are not mixtures of disordered graphite, graphene, and graphane, as observed in other natural and anthropogenic nanoscale carbons (e.g., refs. [37][38][39][40][41][42]. A number of other internal textures were observed.…”
Section: Resultsmentioning
confidence: 96%
“…The 16 O/ 18 O ratios range from 300 to 550 ( 16 O/ 18 O = 499), but are normal within error for most of the samples. Hoppe et al (1995) and Croat et al (2008) concluded that the O-isotopic composition reflects dilution with normal O at some time after grain formation. The dilution process probably occurred in the solar nebula, in the parent asteroid, and in the laboratory.…”
Section: And O Isotopesmentioning
confidence: 99%
“…While all these grains, with the exception of iron oxide, as well as presolar Si 3 N 4 (Nittler et al, 1995), were located by single grain analysis of acid residues, presolar silicates were discovered by isotopic imaging of chemically untreated interplanetary dust particles (IDPs (See Chapter 1.8)) , meteoritic grain-size separates and polished sections (Nagashima et al, 2004;Nguyen and Zinner, 2004), and Antarctic meteorite samples (Yada et al, 2008). Finally, titanium-, zirconium-, and molybdenum-rich carbides, cohenite ((Fe,Ni) 3 C), kamacite (Fe-Ni), rutile (TiO 2 ), oldhamite (CaS), elemental-iron and ruthenium-iron metal, and iron and nickel silicide (Fe 2 Si, Ni 2 Si) were found as tiny subgrains inside of SiC grains and graphite spheres (Bernatowicz et al, 1991Croat et al, 2003Croat et al, , 2008Croat et al, , 2011aCroat et al, ,b, 2012Hynes et al, 2010Hynes et al, , 2011. While TiC inside of a SiC grain (Bernatowicz et al, 1992) could have formed by exsolution, there can be little doubt that interior grains in graphite must have formed prior to the condensation of the spherules.…”
Section: Historical Backgroundmentioning
confidence: 98%